Effects of chronic cochlear electrical stimulation after an extended period of profound deafness on primary auditory cortex organization in cats. (10th December 2013) - Fallon, James B.; Shepherd, Robert K.; Irvine, Dexter R. F.
Abstract Extended periods of deafness have profound effects on central auditory system function and organization. Neonatal deafening results in loss of the normal cochleotopic organization of the primary auditory cortex (AI), but environmentally‐derived intracochlear electrical stimulation, via a cochlear implant, initiated shortly after deafening, can prevent this loss. We investigated whether such stimulation initiated after an extended period of deafness can restore cochleotopy. In two groups of neonatally‐deafened cats, a multi‐channel intracochlear electrode array was implanted at 8 weeks of age. One group received only minimal stimulation, associated with brief recordings at 4–6‐week intervals, over the following 6 months to check the efficacy of the implant. In the other group, this 6‐month period was followed by 6 months of near‐continuous intracochlear electrical stimulation from a modified clinical cochlear implant system. We recorded multi‐unit clusters in the auditory cortex and used two different methods to define the region of interest in the putative AI. There was no evidence of cochleotopy in any of the minimally stimulated animals, confirming our earlier finding. In three of six chronically stimulated cats there was clear evidence of AI cochleotopy, and in a fourth cat in which the majority of penetrations were in the anterior auditory field there was clear evidence of cochleotopy in that field. The finding that chronic intracochlear electrical stimulation after an extended period of deafness is able to restore cochleotopy in some (but not all) cases has implications for the performance of patients implanted after an extended period of deafness.